Influences of personal and social factors on employability among youth from marginalized communities - Armum, Puspalathaa; Osman, Kamisah (International Journal of Asian Social Science, 2023)
The research focused on the employability of youth from marginalised community in Malaysia. Therefore, the research aimed in investigating impact of personal and social variables in influencing employability of the Malaysian youth from marginalised community. Quantitative research design that uses questionnaire were selected by researcher in conducting the research. Around 1181 Malaysian youth at the age range from 15 to 25 years old from marginalised community were selected to participate in this study. Probability sampling method were used in selecting the participants of the study. The study applied a correlational research design whereby a conceptual model was developed. Findings of the study showed positive association between personal variables (self-efficacy, self-esteem and self-determination) and employability of the Malaysian youth from marginalised community. Hence, youth with high self-efficacy, self-esteem and self-determination reported to have higher employability. Besides that, outcome of the study showed positive association between social variables (parental influences, socioeconomic status and role model) and employability of the Malaysian youth from marginalised community. A youth with higher parental influences, socioeconomic status and role model has higher employability. This research developed a model of theory that explains the influences of personal and social variables on employability of Malaysian youth from marginalised community. So, it can be an effective references and guidance in assisting the Malaysian youth from marginalised community towards career development.